Pengaruh Corporate Governance terhadap Nilai Perusahaan pada Perusahaan Perbankan yang Terdaftar di BEI Tahun 2011-2014 - Andy Meindarto; Fitri Lukiastuti (Telaah Bisnis, 2017)
Abstract This study aims to determine the effect of corporate governance on corporate value with the quality of earnings as an intervening variable. Corporate governance mechanism uses four variables managerial: ownership, institutional ownership, the proportion of independent directors and audit committee. The sample consist of 28 banking companies in 2011-2014. The research used Multiple Linear Regression Analysis to test the influence of independent variables on dependent variable. Varible of earnings quality that measured by DA (Discretionary Accrual) has effect on firm value. Institutional ownership of independent board and audit committee have effect on earning quality. Other variables such managerial ownership and institutional ownership have no effect on earnings quality. Institutional ownership and independent board have effect on firm value, meanwhile managerial ownership and the audit committee have no effect on firm value. The value of adjusted R2 for the effect of corporate governance mechanisms on the quality of earnings was 0.170 or 17%. While the value of adjusted R2 for the effect of corporate governance mechanisms on firm value with the quality of earnings as an intervening variable was 0.311 or 31.1%.